Existence of Lagrangians for the Yang-Mills equations - Aldrovandi, R. [UNESP]; Pereira, J. G. [UNESP] (Elsevier, 1988)
The Yang-Mills equations only admit a Lagrangian for gauge groups which are either semisimple or Abelian, or a direct product of groups of both kinds. © 1988.